Goiter and deaf mutism. - Thieme, E T (1975)
The occurrence of deaf-mutism and goiter unassocaited with creatinism or mental retardation in euthyroid patients is known as Pendred's Syndrome. It is considered due to a single mutant recessive gene responsible for both the goiter and deafness. The penetrance is high, the intenseness of expressivity may vary within the same family and only one generation is affected. The extremely atypical hyperplasia seen in such goiters has been considered malignant. In 1956 the author reported a family in which 4 of 6 sibilings demonstrated Pendred's Syndrome. Three of the 4 had undergone thyroidectomy, two were considered to have carcinoma. Nineteen years later the family is again reported. The fourth sibling has recently undergone thyroidectomy. This thyroid demonstrated the same atypical hyperplasia as seen in the elder two siblings. The 19 year followup of this family has shown no evidence of recurrence or metastases, indicating that the atypical hyperplasia is probably not malignant. Pendred's Syndrome is described and certain suggestions are made for the counseling of the parents and the treatment and counseling of those children so afflicted.